2010
DOI: 10.1161/circresaha.109.208645
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Selective Overexpression of Human Angiotensin-Converting Enzyme Type 2 Attenuates Neurogenic Hypertension

Abstract: T he renin-angiotensin system (RAS) is well known for its physiological and pathophysiological roles in the regulation of blood pressure (BP) and cardiovascular function. 1,2 A new component of the RAS, angiotensin-converting enzyme (ACE) type 2 has been identified, from human heart failure ventricle and lymphoma cDNA libraries (reviewed elsewhere 3,4 ). Although the angiotensin-converting enzyme type 2 (ACE2) transcript was first described in heart, kidney and testis, additional studies reported ACE2 mRNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
175
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(188 citation statements)
references
References 39 publications
11
175
1
1
Order By: Relevance
“…Given that ACE2 mediates antihypertrophic effects in cardiomyocytes (15), it is conceivable that progressively increasing cardiac ACE2 activity during gestation may regulate growth of the myocardium. Central overexpression of ACE2 downregulates AT 1 R expression in the brain, attenuates hypertension, and improves arterial baroreflex induced by Ang II infusion or in spontaneously hypertensive rats (13). Collectively, these findings indicate a critical role for ACE2 in the central regulation of blood pressure and the development of hypertension.…”
Section: Ontogeny Of Ace2mentioning
confidence: 76%
See 1 more Smart Citation
“…Given that ACE2 mediates antihypertrophic effects in cardiomyocytes (15), it is conceivable that progressively increasing cardiac ACE2 activity during gestation may regulate growth of the myocardium. Central overexpression of ACE2 downregulates AT 1 R expression in the brain, attenuates hypertension, and improves arterial baroreflex induced by Ang II infusion or in spontaneously hypertensive rats (13). Collectively, these findings indicate a critical role for ACE2 in the central regulation of blood pressure and the development of hypertension.…”
Section: Ontogeny Of Ace2mentioning
confidence: 76%
“…Genetic inactivation of angiotensinogen, renin, ACE, or AT1R in mice causes abnormal glomerular and renal vascular development, pelvic dilation (hydronephrosis), and hypoplastic papilla (10). Accumulating evidence indicates that ACE2 plays an important role in the regulation of cardiac structure and function (11), age-related glomerulosclerosis (12), central regulation of blood pressure (13), and acute lung injury (14). To our knowledge, the expression and the role of ACE2 during kidney, lung, heart, and brain development is largely unknown.…”
mentioning
confidence: 99%
“…92 In addition, ACE2 overexpression in the brain prevented the Ang II-mediated decrease in NOS expression in regions involved in blood pressure regulation. 93 Zhang et al 94 reported that the central administration of Ang-(1-7) stimulates NO release and upregulates eNOS in a rat model of cerebral ischemia/reperfusion, further corroborating the antioxidant actions of ACE2 in the brain.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 79%
“…Rats were infused ICV with artificial cerebrospinal fluid (ACSF; in mmol/l) 147 NaCl, 2.9 KCl, 1.6 MgCl 2 , 1.7 CaCl 2 , and 2.2 dextrose) 35 for two weeks. In the same way, the ICV administration of valsartan (100 nmol/day, 2 weeks) 36 and angiotensin (1-7) (4.8 ”mol/day, 2 weeks) 37 in single or in combination were given in volume of 5”l (ACSF) in both lateral ventricles by using a Hamilton microsyringe. Hamilton microsyringe positioned in the injection cannula and the syringe was kept in place for 2 minutes in order to allow for the diffusion of the injected volume and prevents pressure-induced damage.…”
Section: Surgery and Intracerebroventricular Administration Of Valsarmentioning
confidence: 99%